Co-located dual-wave ultrasonics for component thickness and temperature distribution monitoring. (March 2023) - Zhang, Yifeng; Cegla, Frederic
Permanently installed ultrasonic sensors have found increasing applications in the field of structural health monitoring (SHM), in particular with respect to thickness measurement and corrosion monitoring. As ultrasonic velocity is temperature dependent, the state and temperature distribution of a component contribute to much of the measurement uncertainties of an ultrasonic SHM system. On the other hand, the temperature dependency of ultrasonic velocity has also led to various temperature sensing methods for measuring temperature distributions within solid materials. While conventional ultrasound-based techniques can measure either a component's thickness at a given temperature, or the internal temperature distributions at a given component thickness, measurement fluctuations and drifts can occur if both variables are set to change simultaneously. In this study, we propose a dual-wave approach to overcome the limitations of the existing methods. 'Co-located' shear and longitudinal pulse-echo measurements are used to simultaneously track the thickness change and through-thickness temperature variation of a steel plate in complex environmental conditions. Results of the verification experiments showed that, in the given conditions, the proposed dual-wave correction method could reduce thickness measurement uncertainties by approximately a factor of 5 and eliminate 90% of the drift in temperature predictions.